Students’ Perception Towards Idiomatic Speaking Class: A Study at Foreign Language Center Students - Lasmini, Lasmini; Wati, Laila; Maysuroh, Siti; Nazri, M. Adib (Humanitatis : Journal of Language and Literature, 2024)
Learning idioms requires appropriate teaching methods to facilitate students’ understanding, especially when teaching speaking. Therefore, the research examined how teaching idioms affected students’ speaking skills and perceptions of the learning experiences. The research was conducted at the Foreign Language Center (FLC) students in Selong, East Lombok Regency, using qualitative and quantitative methods, focusing on detailed descriptions and analysis, as well as surveys to investigate social or humanitarian issues. The results showed that 68.75% of students enjoyed learning idioms and felt the class improved their speaking abilities. Meanwhile, about 50% of students experienced difficulty memorizing idioms and correct pronunciation. Interactive teaching methods could make learning more enjoyable. Students gained confidence and fluency in using idioms, despite initial difficulties with pronunciation and memorization. Overall, the study concluded that teaching idioms enhances English speaking skills and student motivation.